The Effectiveness of Augmented Reality App to Improve Students Achievement in Learning Introduction to Animals - Nisaun Markamah; Subiyanto Subiyanto; Agus Murnomo (Intelektual Pustaka Media Utama, 2018)
In this experimental study, AR book app is used to improve student learning outcome of kindergarten in animals introduction subject. AR book app is an application based on Augmented Reality (AR) technology that adapts the kindergarten curriculum in Indonesia. AR book app has included 3D view and animals video. 3D based learning makes it easy for students to visualize learning materials and video-based learning to makes students give attention when learning activity. In a field experiment at kindergarten, 111 kindergarten students were divided into two groups participated in the learning activity that using different learning media. The two groups were group A and group B. Group A is an experimental group which taught using Augmented Reality (AR) book app. Group B is control group which taught using group note methods. Experimental result showed that students’ performance in learning improved significantly by using Augmented Reality (AR) book app media. In this study, students indicated that the experimental group learning outcome is better than the control group.